TINJAUAN HUKUM TENTANG IMPLEMENTASI TUGAS DAN FUNGSI BADAN PENGEMBANGAN SUMBER DAYA MANUSIA PROVINSI RIAU DALAM RANGKA PENGEMBANGAN KOMPETENSI PEGAWAI NEGERI SIPIL - Hadra Nafila Fajriani; Evi Deliana; Muhammad A. Rauf (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The smooth implementation of government tasks and national developmentis highly dependent on the working mechanism of the state apparatus, especiallycivil servants. Civil Servants, hereinafter abbreviated as PNS, are not onlyelements of the state apparatus, but also public servants who live in the midst ofsociety and work for the benefit of society. The position and role of civil servantsin every government organization is very decisive, because civil servants are thebackbone of the government in carrying out national development.This study is based on the fact that it is important to develop humanresources by increasing skills to create administrative officers who are competentin the field of human resource management. The purpose of this study was toexamine and analyze human resource development through capacity building atthe Human Resource Development Board of Riau Province.This research is sociological legal research, namely research that looks atthe relationship between law and society with the gap between the law that shouldand the law that actually occurs. This research was conducted at the HumanResources Development Board of Riau Province. This research also containsinterviews distributed to civil servants who participated in competencydevelopment and those who did not participate in competency development. Thedata collection technique was carried out by interviews and literature review.From the results of research that has been done, the implementation hasbeen going quite well. This is because the relevant agencies are moving throughupdates for employees in competency development. The inhibiting factors areadministrative sanctions that have not gone well and the limited budget of fundsowned.Keywords: Competency Development, Civil Servants.